Time interval distribution of hepatitis B vaccine immunization among infants in China from 2017 to 2021 - Sihui Zhang; Xiaoling Tian; Li Wang; Ming Liu; Chao Wang; Tianshuo Zhao; Xianming Cai; Xiyu Zhang; Mingting Wang; Juan Du; Yaqiong Liu; Qingbin Lu; et al. (Human Vaccines & Immunotherapeutics)
Infant hepatitis B vaccine coverage in China is high, with over 95% of infants immunized; however, high vaccine coverage can often mask low timeliness. The vaccination interval between the second and third doses is not clearly defined by immunization guidelines in China. This retrospective cohort study assessed the time interval distribution of hepatitis B vaccination among a cohort of randomly selected live births from the Centers for Disease Control and Prevention across four provinces or municipalities in China between January 2017 and December 2021. Among the infants analyzed, 163,224 received the first dose of hepatitis B vaccine with 146,905 (90.0%) and 135,757 (83.2%) infants receiving the second and third doses, respectively. A total of 132,577 (90.2%) infants received the second dose between 28 and 61 days after the first dose. Of the 119,437 (88.0%) infants that completed the hepatitis B series between 61 and 214 days after the second dose 87,067 (64.1%) infants were vaccinated with the third dose between 151 and 180 days after the second dose. The time interval distribution varied across the four provinces or municipalities (p < .001). Of the 58,077 infants who completed the hepatitis B vaccine series, 36,377 (62.6%) infants used the same type of hepatitis B vaccine for all three doses. Overall, the timeliness of hepatitis B vaccination for infants was lower than expected, with regional disparities observed. This highlights the need for improved timeliness through the introduction of a defined timeframe for the last two doses of vaccine and training for obstetricians and related personnel.